Reaction of dissolved ozone in hydrogen peroxide produced during ozonization of an alkaline medium in a bubble column - doi: 10.4025/actascitechnol.v36i1.11834 - Cremasco, Marco Aurélio; Mochi, Vanessa Trevizan (Acta Scientiarum. Technology, 2014)
The effect of a reaction of dissolved ozone in an alkaline water solution with hydrogen peroxide was evaluated. Assays were conducted in a bubble column with a gaseous ozone concentration (mixed with oxygen) at 21 and 27 g m-3. Concentration curve of dissolved ozone in the liquid revealed an ozone concentration peak in the liquid phase, subsequent decreasing concentration and constant maintenance in the stationary phase. Highest concentration was not detected for the lowest ozone concentration in the gaseous phase. Peak was due to the self-decomposition of ozone in the liquid phase and the production of hydrogen peroxide. The latter reacted with molecular dissolved ozone and decreased ozone concentration after maximum concentration.